Social Media As Alternative Media For Arabic Teaching In Digital Era - Azkia Muharom Albantani (ALSINATUNA, 2019)
The article aims to reveal the role of electronic social media such as youtube, instagram, and facebook as alternative media for Arabic teaching. The article employed a qualitative method through literature approach revealing phenomenon that are developing in the Arabic teaching. It is true that the three social media are alternative media that can be used by teachers in teaching Arabic. Students of elementary to secondary school, further students of college commonly use the three social media. The use of social media in the learning process is very likely may improve students’ motivation and interest. In addition, Arabic teaching will of course not bordered by space since it can be conducted anywhere.